The Resin Industry in India and some Suggestions for its Improvement - Tiwari, K. M. (Indian Forester, 1968)
The resin industry of India though began more than seventy-five years ala is still backward in many respects. If it fails to improve in the near future it will not be able to survive. Among other measures the following steps should be taken without any delay. (i) The practice of early and adequate thinnings in chir stands should be followed rigidly so that trees reaching tappable size are composed of Individuals of good ferm and vigour with a good crown-length ratio. (ii) In all areas where regeneration of chir crop is being attempted, high resin yielders of good form should be left as seed bearers (iii) Immediate steps should be taken to develop superior racial strains capable of yielding higher quantities of resin. (iv) Research to impreve the yield of resin by application of sulphuric acid paste and 2, 4-D chemical should be Initiated at once and the results already obtained should be translated In the field. (v) The processing of crude resin should be done as far as possible by modern plants. (vi) Research should be Initiated to find eat alternative uses of resin and turpentine.